Nursing care of a premature newborn hospitalized in the neonatal intensive care unit - Rozalska-Walaszek, Ilona; Lesiuk, Witold; Aftyka, Anna; Lesiuk, Leszek (Nursing Problems / Problemy Pielęgniarstwa, 2012)
A patient treated in the Neonatal Intensive Care Unit (NICU) requires a specialized nursing care and its quality plays a significant part in prognosis. The smaller and younger the patient, the morefrequent life-threatening conditions occur and the higher the mortality rate. Therefore, nurses and midwives are important members of healthcare team who are supposed to be well-educated on both the physiological differences and factors which hinder prematures from adopting to the external environment. The article focuses on the main problems and rules concerning nursing care of prematures in the NICU. Skin care is of vital importance. The integument protects the body from dehydration and injury, is part of the temperature-regulating mechanism of the body as well as acts as a sense organ. Thus, it plays a role in communication with the newborn. The research shows that positive stimuli influence the development of the central nervous system and have a calming effect providing a sense of security.